Hubungan antara Cyberbullying dengan Kenakalan Remaja - Widjijati Widjijati; Herry Prasetyo (Prodi Keperawatan Purwokerto, 2019)
The use of the internet cannot replace from everyday life. UNICEF research results show internet users in Indonesia who come from among children and adolescents are predicted to reach 30 million. The development of information technology has made cyberspace a place for online violence or cyberbullying. This study aims to find out the relationship between cyberbullying with juvenile delinquency. This study used a descriptive correlational design with a cross sectional design. Data were analyzed with the Spearman Rank trial. The study showed that the correlation between cyberbullying with juvenile delinquency is very weak with the value of the coefficient of weakness of 0.161. This result is also strengthened by the significance value of 0.78 which means that the significance value α (0.05). It can be concluded based on statistics that there is no relationship between cyberbullying with juvenile delinquency.